(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
A study of Kinetic reactions of Disproportionation reaction under Alkaline conditions. Transitionmetals have many industrial and research applications. Also, many biological systems have transitionmetal ions as cofactors. One of the most extensively studied transition metals is Manganese. Under acidicconditions Anal R grade H,SO, state is very stable, however, under alkaline condition H,SO4, is readilyoxidized to Mn3+ state. In solution, Mn3+ state disproportionate to Mn2+ state and Mn4+ state. Resultsfrom this study show that oxidation of 2N H₂SO4, to Ce(SO4), state can take place in the presence orabsence of oxygen. Potassium hexacyanoferrate (III) of GR (S. Merch) grade was used for preparing itsstandard solution’ by dissolving its required weighed amount in known volume of doubly distilled waterstandard solution of ceric sulphate was prepared by dissolving its BDH (Technical) grade sample in 2NH₂SO4, solution of Anal R grade H,SO, while heating during the preparation of Ce(SO4), solution watershould be added frequently until the sample was fully dissolved. In no case concentration of solutionshould have H₂SO4, by than 0.5 N otherwise a precitutate will be obtained due to hydrolysis of the salt.The overall strength of H₂SO4 in hexacyanoferrate (III) values obtained at different hexacyanoferrate (III]was used to determine order to reaction with respect to hexacyanoferrate (III).